Optimalisasi Prestasi Belajar Materi Pembelaan Negara Melalui Pendekatan Mastery Learning di SMP - Priyanta, Priyanta (Universitas Muhammadiyah Surakarta, 2015)
This research surrounded by still have not optimal of domination of matter Country of Protection among student and implementation of approach of mastery learning. This research aim to description about optimalisation of domination of matter Country protection through approach of mastery learning in study of Education Citizenship at class student IX C State Junior High School Two Cawas Region Klaten even semester of school year 2013/2014. Subject and research data source is 20 students. Data collecting method applies observation, documentation, and test. Data analysis applies critical analysis and comparability. Indicator success of using KKM 75 and complete target of class 100%. Research procedure applies cycle. Result of research and solution it is by know that data obtained from finite precycle of cycle II, obtained progress of achievement of student learning in study of Education Citizenship with matter Country of Protection through approach of mastery learning, at precycle average of 72,1 and cycle I average of 73,9 and cycle II average of 86,2. From this data, seems to explain that happened increase of average of value from precycle to cycle I 1,8 numbers (2,5%), from cycle I to cycle II happened increase 12,3 numbers (16,6%), from pasiklus to cycle II happened increase 14,1 numbers (19,6%). Highest value of phase precycle 80 and cycle I 82 and cycle II 96. Seems to explain that from phase precycle to cycle I happened increase equal to 2 number (2,5%), from cycle I to cycle II happened increase14 numbers (17,1%), and from precycle to cycle II happened increase 16 numbers (20%). Low value of phase precycle is obtained by 64 and cycle I 68 and cycle II 78. thereby, can be affirmed that from phase precycle to cycle I happened increase equal to 4 number (6,3%), from cycle I to cycle II happened increase 10 numbers (14,7%), and from precycle to cycle II happened increase 14 numbers (21,9%). Complete percentage learnt starts from precycle is obtained equal to 20% and cycle I is obtained equal to 30% and cycle II equal to 100%. Seems to explain that from phase precycle to cycle I happened increase equal to 10%, from cycle I to cycle II happened increase equal to 70%, and from precycle to cycle II happened increase equal to 80%. Thereby, achievement of student learning in study of Education Citizenship with matter Country of Protection through approach of mastery learning from finite precycle of cycle II happened increase significant.